The Emancipation of Women in Waqf (Study of Hadith) - Monady, Hanief (AL-QARDH, 2022)
The emancipation of women became important in all aspects of the field. Women have the same rights and obligations as stated in the philosophy of the birth of women's emancipation. Likewise, in waqf, one of the forms of philanthropy in Islam, the emancipation of women is also found in the field of waqf. This is reflected in several hadiths of the prophet Muhammad PBUH which explain how women participate in the field of waqf. If some of the hadiths of the prophet Muhammad PBUH about almsgiving, zakat, infak, and waqf are carefully and deeply observed, then there is a reflection of the woman who took part in its implementation. This is what is to be captured in this paper regarding how the emancipation of women is reflected in several hadiths of the prophet Muhammad PBUH which are themed about waqf. The purpose of women's emancipation is to demand equality of women's rights with the rights of men and provides opportunities for women to work, study, and work in balance with their abilities, this is the ultimate goal of this article, that women also have the same rights as men in giving some of their property for representation.